THE CURRENT STATUS OF THE DEVELOPMENT OF A PERFORMANCE MANAGEMENT SYSTEM AND THE APPLICABILITY OF ITS BASIC METHODS IN MUNICIPAL ADMINISTRATIONS - R. Mamedov (Вестник университета)
The existing approaches to the management of municipal entities, the methods of planning used are explored. The main problems and constraints of development of the efficiency management system are singled out. A number of administrations of municipalities of the Moscow region have been surveyed on the use of methods for planning and managing the implementation of development programs. It was concluded that there is a lack of awareness and a weak nature of the use of well-known and well-proven methods in business. The main recommendations for the development of a methodological framework for the development and implementation of economic programs of municipal administrations and, in particular, for a more extensive application of modern tools for performance management have been formulated.